Performance in professional soccer players: normative data and benchmarks from official matches for metabolic power and high-intensity activities - Laterza, F; Manzi, V. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: The opportunity to compare data among players using normative data and benchmarks may represent a helpful tool for coaches to assess the players` physical performance easily and quickly. This study aimed to create normative data and benchmarks that can be exploited to compare professional soccer players` physical capacity competing in the Premier Division Championship (series A).